Routine bacterial screening of platelet concentrates by flow cytometry and its impact on product safety and supply. Issue 3 (3rd December 2014) - Müller, B.; Walther‐Wenke, G.; Kalus, M.; Alt, T.; Bux, J.; Zeiler, T.; Schottstedt, V.
<x xml:space="preserve">Abstract</x> Background and Objectives Bacterial contamination represents the major infectious hazard associated with transfusion of platelet concentrates (PCs). As bacterial screening of PCs is not mandatory in Germany, the BactiFlow flow cytometry test has been introduced as a rapid detection method to increase product safety. Materials and Methods During a period of 25 months, a total of 34 631 PCs (26 411 pooled and 8220 apheresis‐derived PCs) were tested at the end of day 3 of their shelf life using the BactiFlow system. PCs initially reactive in BactiFlow testing and expired PCs not reactive in BactiFlow on day 3 were also investigated by the BacT/ALERT system and by microbiological cultivation in order to identify the contaminating bacterial species and to confirm reactive BactiFlow results. Results Two hundred and twenty‐eight PCs (0·7%) had an initially reactive result, 24 of them remained reactive in a second test run. Out of these reproducible reactive BactiFlow results, 12 could not be verified by parallel BacT/ALERT culturing, resulting in a confirmed false‐positive rate of 0·03%. The bacterial species were identified as S. aureus, S. epidermidis, S. dysgalactiae ssp. equisimilis and B. cereus. In 10 out of 9017 expired PCs (0·11%), a confirmed‐positive result was obtained in the BacT/ALERT system which had a negative result in the BactiFlow system. Conclusion Testing of PCs by BactiFlow was successfully implemented in our blood donation service and proved sufficient as a rapid and reliable screening method. False reactive results are in an acceptable range since the transfusion of 12 bacterially contaminated PCs was prevented.